THE KHUBSUGUL PHOSPHATE-BEARING BASIN: NEW DATA AND CONCEPTS - Ilyin A.V. (My University, 2004)
The Khubsugul phosphate-bearing basin divided into the western and eastern zones. Phosphorites composed of alternating structureless phosphate layers (1–3 cm) and thinner lenticular dolomite laminae prevail in the western zone corresponding to the distal part of the sedimentation profile. Contents of all trace elements are approximately equal and correspond to the clarke level in both phosphate and dolomite layers. The laminae are also identical in terms of the low (–7 PDB) 13 values. Phosphorites of the western zone were rapidly buried and the presence of dolomite intercalations is explained by postsedimentary segregation. The eastern proximal zone is dominated by the so-called dolomitic phosphorites with variable-size irregular fragments of phosphate matter enclosed in the later dolomitic matrix. Relative to structureless varieties, granular (pelletal) phosphorites of the basin are subordinate and enriched in trace elements (particularly, rare earth elements). Phosphate facies are replaced by black shales on the western side of the basin.